Use of fetal fibronectin testing in women transferred for threatened preterm labour in remote far north Queensland. (3rd September 2018) - Downing, Sandra G.; Wright, Rebecca; Marquardt, Tonia; Callander, Emily
Abstract : Background: Threatened preterm labour is a common reason for medical transfer from remote communities; however, many transferred women do not deliver preterm. A tool for prediction of preterm birth such as fetal fibronectin may reduce transfers and related social and economic costs. Aim: To review the use of fetal fibronectin testing in women transferred for threatened preterm labour from Cape York to Cairns Hospital between 2011 and 2015 and determine the role testing could play in reducing transfers and associated costs. Materials/methods: Records from the Royal Flying Doctor Service and Cairns Hospital were accessed. Women transferred solely for threatened preterm labour were included in the study. Fetal fibronectin testing, hospital admission, outpatient stays and birth outcome data were collated and analysed. Costs were assigned using the National Hospital Cost Data Collection, round 19. Results: Forty‐seven women were included in the study; however, only 20 underwent fetal fibronectin testing. Transfer of 30 women who had either a negative test or were not tested but delivered at term resulted in 41 inpatient nights and 443 excess outpatient nights, costing an estimated AU57 408. Aeromedical transfers were estimated to cost a further 151 500. Conclusion: Adherence to clinical guidelines and greater availability and use of fetal fibronectin testing in Cape York have the potential to reduce aeromedical transfers for threatened preterm labour. Substantial inpatient and excess outpatient stays could be avoided with associated reduction in health system and social costs. Strategies to improve adherence to guidelines and increase access to testing are required.